2019
DOI: 10.1098/rspb.2018.2852
|View full text |Cite
|
Sign up to set email alerts
|

Geography of speciation affects rate of trait divergence in haemulid fishes

Abstract: Speciation and the interactions between recently diverged species are thought to be major causes of ecological and morphological divergence in evolutionary radiations. Here, we explore the extent to which geographical overlap and time since speciation may promote divergence in marine species, which represent a small fraction of currently published studies about the patterns and processes of speciation. A time-calibrated molecular phylogeny of New World haemulid fishes, a major radiation of reef and shore fishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 74 publications
1
8
0
Order By: Relevance
“…Nonetheless, similar to our findings, a recent study of haemulid fishes found that the level of divergence in phenotypic traits and colour of sister species, including those that occur in allopatry, was uncorrelated with time since divergence (Tavera and Wainwright 2019). Furthermore, studies focused on individuals within fish populations have suggested that morphological change and associated diet specialisation occurs at an early ecological and evolutionary stage of divergence, and before lineage diversification (Kusche et al 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Nonetheless, similar to our findings, a recent study of haemulid fishes found that the level of divergence in phenotypic traits and colour of sister species, including those that occur in allopatry, was uncorrelated with time since divergence (Tavera and Wainwright 2019). Furthermore, studies focused on individuals within fish populations have suggested that morphological change and associated diet specialisation occurs at an early ecological and evolutionary stage of divergence, and before lineage diversification (Kusche et al 2014).…”
Section: Discussionsupporting
confidence: 90%
“…Most comparable analyses of marine fishes have found a higher prevalence of allopatry between sister species, from 62% in New World haemulid fishes (N = 42 spp. ; Tavera and Wainwright 2019), to 64% in parrotfishes (N = 61 spp. ; Choat et al 2012), to 88% in Halichoeres wrasses (N = 24 spp.…”
Section: Patterns Of Carangoid Sympatry and Allopatrymentioning
confidence: 99%
“…Few studies have applied analyses of age-range correlation and range symmetry in large and taxonomically inclusive lineages of vertebrates, particularly marine fishes (Fitzpatrick and Turelli 2006; Phillimore et al 2008; Wollenberg et al 2011; Mora et al 2012; Anacker and Strauss 2014; Hodge and Bellwood 2015; Tavera and Wainwright 2019). The use of such approaches is hindered by lack of comprehensive taxon sampling and availability of range data for many species.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the extensive geographic distribution, with a marked spatial overlap of sibling species, has revealed that besides vicariant events, ecological speciation also participates in the evolutionary diversification of this family of fishes . In fact, in this family, recurrent sympatric speciation processes occurring in short periods of time (∼5 M.a), especially in species of the genus Haemulon, have been observed (Tavera et al, 2012;Tavera and Wainwright, 2019); recent events of genetic introgression have also been observed in some cases (Bernal et al, 2017). In ecological speciation processes, with the fragmentation of ecological niches, in general, the split of the gene pool occurs without remarkable genetic changes or high selection pressures (Rocha and Bowen, 2008), thereby producing less propitious conditions to fix conspicuous chromosome rearrangements.…”
Section: Extrinsic Environmental Factors and Karyotype Conservatism Imentioning
confidence: 99%
“…Grunts are smallto-medium-sized carnivorous fishes that predominantly inhabit rocky substrates at a low depth (Nelson et al, 2016). This group has conservative karyotypes (Motta-Neto et al, 2012), a wellknown phylogenetic relationship Tavera et al, 2012), and several examples of sibling-species divergence in the New World (Tavera et al, 2018;Bernal et al, 2019;Tavera and Wainwright, 2019), making it a good model for the evaluation of slow chromosome changes in a space-temporal context.…”
Section: Introductionmentioning
confidence: 99%